Students’ Perception of Self-Assessment in Assessing Writing Skill during Online Learning - Astitiani, Made; Dewi, Ni Luh Putu Eka Sulistia; Paramartha, .A. Gede Yudha (Universitas Pendidikan Ganesha, 2022)
Distance learning makes the assessment process in the classroom less effective, especially for assessing writing skills. Therefore, self-assessment is implemented to form independent and competent students in the field of writing. The results of initial observations showed that students had different perceptions regarding the application of self-assessment in assessing writing skills during online learning. This study aims to analyses the perceptions of 5th semester students majoring English Language Education regarding self-assessment in assessing writing skill during online learning. To achieve this objective, the researcher used a mixed method with questionnaire and interview as research instruments. The results of the questionnaire analysis showed that the average of each dimension was 45.38 for the memory dimension; 53.35 for the evaluation dimension, and 35.74 for the impression dimension. From the results of the analysis, it can be seen that students have positive perceptions on the memory and impression dimensions, and negative perceptions on the evaluation dimensions. Based on these results, it is concluded that self-assessment provides advantages and disadvantages for students in assessing writing skills during online learning.